High Performance Coaching
This is the National Coaching Foundation's web site dedicated to the High Performance Coaching Community. A source for immediate information, research, online events, document exchange, and a forum for discussion. Those here are the World-Class Programme coaches and the support team working with those coaches; all dedicated to the international performance of our athletes.